FAKTOR YANG MEMPENGARUHI TINGKAT KUNJUNGAN TAMAN TEMATIK: STUDI KASUS TAMAN SKATEBOARD PALEMBANG - Fran Sinatra; Helmia Adita Fitra (Jurnal Perencanaan dan Pengembangan Kebijakan, 2021)
The realization of sustainable development goals is a major concern today. Related to the development of urban areas, this goal is contained in the 11th goal, which is to create sustainable cities and communities. One of the efforts to achieve this goal is through the provision of good public open spaces. Public open space has a role as a space for interaction and social space for its people. The development of thematic parks is one of the efforts to maximize the social benefits of public open spaces so that sustainable urban and community development can be realized. This study aims to identify the factors that influence visits to thematic parks. The method used is descriptive quantitative method using regression analysis. The incidental sampling technique used in this study, where the respondents were park visitors. The results show that the factors that greatly affect the frequency of thematic park visits are influenced by gender and interactions in the community, while other factors such as age, distance, and dominant factors.